Implementación de un plan de marketing y su impacto para el desarrollo turístico cultural en los turistas del cantón Ventanas año 2022 - Veliz Ponce, Deryan David (2022)
In such virtue I have put in consideration the Implementation of a marketing plan and its impact for the cultural tourist development in the tourists of the canton Ventanas has as objective, to position and to make known the tourist attractions, by means of a micro evaluation it was possible to identify the current state of the marketing and cultural tourist development also the current situation in the tourists was analyzed, as purposes to improve the quality of life of the inhabitants, it is so that strategies have been considered to reach the tourist development in the Canton Ventanas. The applied research methodology has a qualitative and quantitative approach, which will be exclusively observation and evolution, reflected through surveys, to know the needs. The proposal for the implementation of a marketing plan and cultural tourism development in Ventana is to have an excellent tourism activity with the financing of entrepreneurs who have decided to invest in the city for its economic development lacks advertising in tourism services that potentiate this sector. With the support of the GAD of the canton Ventanas, it will be possible to provide quality services and this will influence the tourist, economic and social development of the canton, and thus meet the prospects of tourists and therefore their visits will be more frequent.